(untitled) (Research, Society and Development, 2023)
Due to the high transmissibility of the coronavirus, entire nations have adopted social confinement measures with profound global socioeconomic impacts and enormous damage to medical education, which for many years was unidirectional. With this, several limitations have arisen regarding teaching, especially medical teaching since the frequency of medical students in hospitals and health-related departments makes them at greater risk of acquiring the disease and may become potential symptomatic or asymptomatic vectors. The use of digital information and communication technologies offers many advantages currently, as in addition to being cost-effective, they allow social isolation, minimizing educational losses. To develop an application that aims to facilitate the teaching-learning process of basic surgical practice for medical students. Methodology: The study was developed from April to November 2021, where the stages of analysis, design, development, and evaluation followed, chronologically obeying these stages based on the Galvis-Panqueva framework. Instrumental Med was developed to facilitate the teaching-learning process in clinical surgery, we used the contents taught in the discipline to develop software capable of contributing and adding to the individual study of students in the clinical cycle of the medical course, through active activities that stimulate learning. We believe that the use of technology can positively contribute to the teaching and learning process of these students, thus reinventing existing forms of study and consequently contributing to their motivation.